Nagsimula sa puso ([s.l.] Vision Film, 2003)
Love truly moves in mysterious ways and sometimes, even if the odds are against you, you would go heaven and earth to fight for it. But are you willing to give up your life for the one that you believe you truly love? Are you willing to turn your back and leave everything in your life for the sake of eternity with someone everyone thinks isn't right for you? This is the story of two individuals who are prisoners of the bitter societal norms. Two people who choose to go against the rigid rules of society to express their love for each other.
VCD
Hilda Koronel, Jay Ilagan, Armida Siguion Reyna, Cherie Gil, Kristine Garcia and Richard Gomez
Keywords: Love stories; Drama; Feature films